1994
DOI: 10.1007/bf01827427
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac pacing does not improve orthostatic tolerance in patients with vasovagal syncope

Abstract: This study was undertaken to assess the value of dual chamber pacing in the treatment of vasovagal syncope. In a preliminary study, on two patients the time to presyncope during head-up tilt before and after implanting pacemakers was determined. Both patients fainted with similar decreases in blood pressure at almost exactly the same time after tilting. In the main study, nine patients with pacemakers implanted as treatment for syncope were studied, in random order, with pacemakers on and either off or turned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…Head-up tilt laboratory findings have generally reported that pacing fails to prevent syncope, although it Task Force Report 1283 may prolong the premonitory warning phase [296][297][298][299][300] . As a result, there is a strong consensus of opinion that cardiac pacing should play only a minor role in the treatment of patients with vasovagal faints.…”
Section: Vasovagal Syncopementioning
confidence: 99%
See 1 more Smart Citation
“…Head-up tilt laboratory findings have generally reported that pacing fails to prevent syncope, although it Task Force Report 1283 may prolong the premonitory warning phase [296][297][298][299][300] . As a result, there is a strong consensus of opinion that cardiac pacing should play only a minor role in the treatment of patients with vasovagal faints.…”
Section: Vasovagal Syncopementioning
confidence: 99%
“…As a result, there is a strong consensus of opinion that cardiac pacing should play only a minor role in the treatment of patients with vasovagal faints. Nevertheless, unlike most other treatment avenues in this condition, pacing has been the subject of a number of both small single/multiple-centre studies [296][297][298][299][300][301][302] , as well as two major multicentre randomized controlled trials [135,303] demonstrating effectiveness in highly select patient populations. In this regard, the strongest supportive evidence is provided in the published report of the North American vasovagal pacemaker study [301] , and the recently reported European VASIS trial [135] .…”
Section: Vasovagal Syncopementioning
confidence: 99%
“…One example of the use of this test was to demonstrate the lack of effect from cardiac pacemakers [5]. Another example was to assess the effects, using a double-blind study, of salt-loading of patients with poor orthostatic tolerance [6].…”
Section: Introductionmentioning
confidence: 99%
“…This approach provokes presyncope in almost all subjects (allowing for symptom recognition in patients with syncope), while discriminating between patients with syncope and healthy controls, with a specificity of 92%, sensitivity of 85%, and repeatability of 1.1±0.6 min 16,17 . This allows not only diagnosis and pathophysiological assessment [19][20][21][22] , but also the evaluation of treatments for orthostatic intolerance due to its high repeatability [23][24][25][26][27][28][29][30] . For these reasons, we argue this should be the "gold standard" for orthostatic stress testing, and accordingly this will be the method described in this paper.…”
mentioning
confidence: 99%